Student Activeness in Problem Solving Ability Based Learning on Magnet Material - Shinta Syafitri; Yanti Fitria (Postgraduate, University of Mataram, 2025)
Education is a conscious and planned effort to create a learning and teaching atmosphere so that students actively develop their potential to have spiritual religious strength, self-control, personality, intelligence, noble morals, and the skills needed by themselves, society, nation and state. Education has a major role in achieving success in child development. Education is a process that is carried out consciously and planned in order to develop the abilities and potential that exist within a person. This study aims to see the effect of implementing the PBL model on students' learning activities and problem-solving abilities on the material of magnetic force in elementary schools. This study uses a quantitative approach with a quasi-experimental design with a pretest-posttest non-equivalent control group design. The results showed that the experimental group that implemented the PBL learning model experienced a significant increase compared to the control group that used conventional learning. The increase in learning activities in the experimental group was recorded at 22.39%, while the increase in problem-solving abilities reached 31%. In contrast, the control group that used conventional methods also showed an increase, but in a lower percentage, namely 20.11% for learning activities and 21.26% for problem-solving abilities. The application of the PBL model is more effective in improving both aspects compared to conventional learning methods.